The Role of Foreign Private Investors in the Industry Development of Nigeria: A Test Case of "X" Breweries Limited - Yusuff, Oyindunla F (Obafemi Awolowo University, 2014)
Most developing economies seek to industrialize as a way to reduce excessive reliance on the agricultural section which is vulnerable to adverse economic conditions. The industrialization pattern is to sponsor programmes promoting the indigenous manufacture of import substitutes. This pattern often involves both local and foreign investment of capital and technical know-how, which invariably is supplied by foreign partners.